2005
DOI: 10.1029/2004jd005469
|View full text |Cite
|
Sign up to set email alerts
|

Interannual consistency of bi‐monthly differences in diurnal variations of the ground‐level, vertical electric field

Abstract: [1] Interyear consistency is demonstrated in the bi-monthly average diurnal vertical electric field measured over $720 ''fair-weather'' days collected during a 5-year interval (1998 to 2002) at Vostok (78.5°S, 107°E; magnetic latitude 83.6°S), Antarctica. After correcting for the influence of polar-cap convection, seasonal peaks in the average electric field values occur around July-August with a diurnal maximum at $ 2050 UT while lowest average magnitudes are measured near November-December when the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 21 publications
6
66
0
1
Order By: Relevance
“…A rapid increase in electric field intensity near the surface of the ice field initiated at varying wind velocities has been reported at Vostok where a diurnal variation in wind velocity commonly occurs (Burns et al 2005). A diurnal wind speed variation is observed nine months a year (data available online from Station Vostok, surface wind and air pressure field, atwww.aari.ru/south/statioris/vostok/ vostok_en.html).…”
Section: Arctic and Antarctic Measure-mentsmentioning
confidence: 96%
See 2 more Smart Citations
“…A rapid increase in electric field intensity near the surface of the ice field initiated at varying wind velocities has been reported at Vostok where a diurnal variation in wind velocity commonly occurs (Burns et al 2005). A diurnal wind speed variation is observed nine months a year (data available online from Station Vostok, surface wind and air pressure field, atwww.aari.ru/south/statioris/vostok/ vostok_en.html).…”
Section: Arctic and Antarctic Measure-mentsmentioning
confidence: 96%
“…Earlier measurements (Bering et al 1998) showed a maximum in the diurnal variation in the 0800-1600 UTC interval for spring/summer and in the 1200-1600 UTC range for autumn/winter, which is different than the maximum in the 1800-2000 UTC period for the Carnegie curve at all times of the year (Israel 1973, p. 353). More recent analysis (Burns et al 2005) shows the Carnegie curve when two-month daily averages are compiled. This improvement is due to careful selection of fair-weather days (39% of the days in a 5-yr period) and correction for the polar-cap ionospheric generator.…”
Section: Arctic and Antarctic Measure-mentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such is the case for the Xanthi site. Applications of that method are found for Marsta Observatory (Israelsson and Tammet 2001), Nagycenk Geophysical Observatory (Märcz and Harrison 2003), and elsewhere (O'Connor 1976; Burns et al 2005) with criteria customized for each site.…”
Section: Resultsmentioning
confidence: 99%
“…Harrison, 2003). At Vostok station, fair-weather data were selected on the basis of electric field values alone, and spikes (change of 50 V m −1 within 5 mins) were rejected (Burns et al, 2005). On most days, the overhead atmosphere at Suva was covered in full or part with cirrus/cirrostratus clouds and a mean solar radiation of 850 W m −2 was recorded near the solar zenith.…”
Section: Instrumentation and Data Selectionmentioning
confidence: 99%